“AN ANALYTICAL STUDY OF FINANCIAL PERFORMANCE OF TATA CONSULTANCY SERVICES” - Trikamlal Patel, Kalpeshkumar (International Journal of Psychosocial Rehabilitation, 2020)
The analysis of financial performance consist of the financial position and results of operations as well as the financial progress of the company are satisfactory or unsatisfactory. The analytical methods or devices are used to ascertain or measure the relationships among the financial statements' items of a single set of statements and the changes that have taken place in these items as reflected in successive financial statements. In this modern era, finance is necessary to each and every business organization, whether it is small or big. Human body can’t survive without blood same as business organization can’t survive in competition market or expansion without finance. Industries are helpful in the growth of Indian economy. So, it is necessary to make financial performance analysis of any company. IT companies provide services such as software support, computer systems design, and data processing facilities management. Here the examples of IT companies are Accenture (Ireland), Infosys Technologies (India), Tata Consultancy (India), and Wipro (India). In this research to study the financial performance of Tata Consultancy Services.